Maternal blood and hair manganese concentrations, fetal growth, and length of gestation in the ISA cohort in Costa Rica - Mora, Ana María (2015)
Background: Animal studies have shown that both deficiency and excess manganese (Mn) may result in decreased fetal size and weight, but human studies have reported inconsistent results. Methods: We examined the association of blood and hair Mn concentrations measured at different times during pregnancy with fetal growth among term births and length of gestation in a cohort of 380 mother–infant pairs living near banana plantations aerially sprayed with Mn-containing fungicides in Costa Rica. We used linear regression and generalized additive models to test for linear and nonlinear associations Results: Mean (7 SD) blood Mn concentration was 24.476.6 μg/L and geometric mean (geometric SD) hair Mn concentration was 1.8 (3.2) μg/g. Hair Mn concentrations during the second and third trimesters of gestation were positively related to infant chest circumference (β for 10-fold increase¼0.62 cm; 95% CI: 0.16, 1.08; and β¼0.55 cm; 95% CI: 0.16, 1.26, respectively). Similarly, average maternal hair Mn concentrations during pregnancy were associated with increased chest circumference (β for 10-fold increase¼1.19 cm; 95% CI: 0.43, 1.95) in infants whose mothers did not have gestational anemia, but not in infants of mothers who had gestational anemia (β¼0.39 cm; 95% CI: 0.32, 1.10; pINT¼0.14). All these associations were linear. Blood Mn concentrations did not show consistent linear nor nonlinear relationships with any of the birth outcomes Conclusions: Mn plays an important role in fetal development, but the extent to which environmental exposures may cause adverse health effects to the developing fetus is not well understood. Among women living near banana plantations in Costa Rica, we did not observe linear or nonlinear associations of Mn concentrations with lowered birth weight or head circumference, as reported in previous studies. However, we did find positive linear associations between maternal hair Mn concentrations during pregnancy and infant chest circunference.